Seabuckthorn juice alleviates allergic symptoms in shrimp-induced food allergy mice - Hong Ren; Xiaofan Zhu; Shiyu Zhai; Xiaoping Feng; Zhuomin Yan; Jiao Sun; Ye Liu; Zhenpeng Gao; Fangyu Long (Food Science and Human Wellness)
Tropomyosin (TM) in shrimp is one of the predominant causes of food allergy around the world. In the present study, the effect of seabuckthorn juice against TM -induced shrimp allergy was investigated in BALB/c mice. Allergic symptoms, spleen index, intestinal section and diarrhea were measured in shrimp allergy mice. As the results, seabuckthorn juice suppressed the lesions in jejunum tissue, diarrhea and allergic symptoms in shrimp allergy mice. Seabuckthorn juice also reduced serum concentrations of tumor necrosis factor-α (TNF-α) as well as immunoglobulin E (IgE) and stimulated the secretion of interleukin-10 (IL-10) in mice with shrimp allergy. Taken together, our findings suggest that increased IL-10 by seabuckthorn juice inhibits Th2 cytokine production to suppress shrimp allergic symptoms. Furthermore, seabuckthorn juice also regulates shrimp allergy by reducing jejunum lesions, inhibiting levels of TNF-α and IgE.